An application of random process for controlled object identification with traffic delay problem - Vu, Tien Viet (H. : ĐHQGHN, 2017)
In the article proposed an effective method estimating transfer function model of controlled plant including dead-time delay, based in stochastic time series of input-output signals. The model structure is modified with parameters optimized until the model error becomes "white-noise" series that with inough smal auto-correlation function.